Effectiveness of phosphonium cation-based ionic liquids as lubricant additive. (June 2016) - González, R.; Bartolomé, M.; Blanco, D.; Viesca, J.L.; Fernández-González, A.; Battez, A. Hernández
Abstract: Two phosphonium cation-based ionic liquids (ILs) were studied as additive to a mineral oil. Solubility tests and TGA of neat samples were performed. Three concentrations of the ILs were used in the tribological tests. Base oil–ZDDP mixtures were used as comparison samples. Tribological tests were made using a reciprocating ball-on-disc configuration. Load ramp and Stribeck curve tests were also performed. The worn surface was studied by different techniques. The results showed similar and better friction reduction properties for ILs- or ZDDP-containing mixtures than the neat base oil. The [P66614 ][(iC8)2 PO2 ]-containing mixtures outperformed the antiwear behavior of the other samples. XPS results showed different mechanisms of lubrication when using ILs or ZDDP. Highlights: Both ionic liquids used as additive showed friction and wear reducing properties. All IL mixtures showed similar friction behavior. [P66614 ][(iC8)2 PO2 ]-containing mixtures showed the lowest wear values. The higher IL concentration showed the better tribological behavior. Friction and wear reduction of the ionic liquids is related to tribofilm formation.